Diagnosis and treatment of primary hyperparathyroidism with pathological fracture of the limbs: A retrospective observational study. Issue 33 (19th August 2022) - Liu, Huijiang; Luo, Kai; Liao, Shijie; Tang, Haijun; Mo, Jianming; Xie, Tianyu; Li, Chong; Li, Boxiang; Liu, Yun; Zhan, Xinli
Abstract : Primary hyperparathyroidism (PHPT) with pathological fracture is rare, and the early symptoms of PHPT lack specificity, leading to misdiagnosis. Therefore, this study aimed to summarize the clinical characteristics and treatment of PHPT patients with pathological fractures and to improve the attention of orthopedic clinicians to PHPT. It is a retrospective study, 2226 patients with hyperparathyroidism in our hospital from 2009 to 2019 were screened, excluding secondary hyperparathyroidism and patients without limb fracture, and the remaining 20 patients with PHPT accompanied by pathological fractures were finally analyzed. Parathyroid hormone (PTH) and calcium levels were compared on the first postoperative day, and the prognosis of the patients was assessed by bone mineral density and Visual Analogue Scale scores at 3 and 12 months postoperatively. The early symptoms of PHPT patients in this study included urinary calculi (80%), bone pain (30%), and digestive tract symptoms (25%). Fourteen (70%) cases were misdiagnosed at the initial diagnosis. After parathyroidectomy, the blood calcium and PTH levels decreased significantly in all patients ( P < .05). For the treatment of fracture, 9 of the patients underwent surgical treatment of the fracture, while the remaining patients received splint external fixation. The follow-up time was 4.60 ± 0.62 years (1–10 years). All patients recovered well from the fracture, the symptoms of systemic bone pain were markedly improved, and bone mineral density was significantly improved after surgery. Orthopedic surgeons need to avoid misdiagnosis and pay attention to the early symptoms in PHPT patients with pathological fracture, and better therapeutic effects can be obtained by combining parathyroidectomy with fractures fixation.